003 OP: CHALLENGES IN QUALITATIVE INQUIRY: JUDGEMENTS OF 'ETHICS' AND 'QUALITY'. Issue 4 (12th April 2015) - Stevenson, F; Gibson, W; Pelletier, C; Park, S; Chrysikou, V
Abstract : Background: UK-based research conducted within a healthcare setting generally requires approval from the National Research Ethics Service. Research ethics committees are required to assess a vast range of proposals, differing in both topic and methodology. We argue the methodological benchmarks with which research ethics committees are generally familiar and which form the basis of assessments of quality do not fit with the aims and objectives of many forms of qualitative enquiry and their more iterative goals of describing social processes/mechanisms and making visible the complexities of social practices. Our research: Drawing on the challenges we encountered gaining ethical approval and subsequently conducting a study of junior doctors' decision-making in an Emergency department, we suggest there is an urgent need to re-think the ways that ethical issues are currently conceptualised. In particular, we argue that embedded in the current paradigm is a restricted notion of 'quality', which frames how ethics are developed and worked through. Specific, pre-defined outcome measures are generally seen as the traditional marker of quality, which means that research questions that focus on processes rather than on 'outcomes' may be regarded as problematic. We illustrate the importance of re-visiting the notion of ethics in healthcare research. Specifically, we consider the need for an alternative 'iterative' paradigm and outline how this offers a useful starting point for moving beyond these limited views. Conclusions: A 'one size fits all' standardisation of ethical procedures and approach to ethical review acts against the production of knowledge about healthcare and dramatically restricts what can be known about the social practices and conditions of healthcare. Our central argument is that assessment of ethical implications is important, but that the current paradigm does not facilitate an adequate understanding of the very issues it aims to invigilate.